2021
DOI: 10.1038/s41467-021-22923-5
|View full text |Cite
|
Sign up to set email alerts
|

A Stat1 bound enhancer promotes Nampt expression and function within tumor associated macrophages

Abstract: Tumor associated macrophage responses are regulated by distinct metabolic states that affect their function. However, the ability of specific signals in the local tumor microenvironment to program macrophage metabolism remains under investigation. Here, we identify NAMPT, the rate limiting enzyme in NAD salvage synthesis, as a target of STAT1 during cellular activation by interferon gamma, an important driver of macrophage polarization and antitumor responses. We demonstrate that STAT1 occupies a conserved ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 83 publications
2
22
0
Order By: Relevance
“…Our RNAseq analysis shows that the Nampt is one of the most IFNg-upregulated genes (Figure 2D; log2 fold-change of 2.1 over control) and is strikingly further potentiated by the co-stimulation of PECs with eN-AMPT (log2 fold-change of 2.75 over control). Accordingly, it has been recently reported that IFNg upregulates iNAMPT expression in a STAT-dependent manner (Huffaker et al, 2021). We confirmed RNAseq results by qPCR analysis.…”
Section: Enampt Boosts Ifng Responses In a Tlr4-independent Mannersupporting
confidence: 88%
See 1 more Smart Citation
“…Our RNAseq analysis shows that the Nampt is one of the most IFNg-upregulated genes (Figure 2D; log2 fold-change of 2.1 over control) and is strikingly further potentiated by the co-stimulation of PECs with eN-AMPT (log2 fold-change of 2.75 over control). Accordingly, it has been recently reported that IFNg upregulates iNAMPT expression in a STAT-dependent manner (Huffaker et al, 2021). We confirmed RNAseq results by qPCR analysis.…”
Section: Enampt Boosts Ifng Responses In a Tlr4-independent Mannersupporting
confidence: 88%
“…There is abundant literature regarding NAMPT and macrophages. Huffaker et al have highlighted the role of intracellular NAMPT (iNAMPT) in mediating the effects of IFNg in tumor-associated macrophages (Huffaker et al, 2021). Such observations prevented us from using specific inhibitors of this enzyme, as they would have had a confounding effect.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, a novel study revealed that STAT1 occupies a conserved element within the first intron of NAMPT. By binding this site, STAT1 can promote NAMPT expression in tumor-associated macrophages ( 45 ). It seems that there is a positive feedback mechanism involving STAT1 and NAMPT.…”
Section: Discussionmentioning
confidence: 99%
“…Both the JAK/STAT1 and JAK/STAT3 signaling pathways participate in macrophage polarization. The JAK/STAT1 signaling pathway can be activated by IFN-γ, which in turn upregulates the expression of nicotinamide phosphoribosyl transferase (NAMPT), the rate-limiting enzyme for NAD salvage synthesis ( 35 ). This study demonstrated that STAT1-induced NAMPT drives glycolysis, M1 polarization, and better outcomes in both mouse and human models of melanoma, while inhibition of NAMPT with FK866 reverses these effects.…”
Section: Targeting Tam Repolarization As a Cancer Treatment Strategymentioning
confidence: 99%